Random access for massive Internet of things:current status, challenges and opportunities - Pingzhi FAN; Li LI; Huan CHEN; Gaofeng CHENG; Linjie YANG; Xiaobo TANG (Tongxin xuebao)
In conventional communication systems, the random access (RA) is a necessary procedure for a user equipment (UE) to establish wireless connection to the network before actual data transmission.Focusing on the massive IoT with large number of nodes, the fundamental characteristics and limitations of conventional grant-based RA were firstly discussed.Then, the grant-free RA, semi-grant-free RA and unsourced RA for massive IoT were addressed in details from multiple perspectives, including their system models, protocol frameworks, algorithm procedures, system performance, related pros and cons, as well as critical challenges and potential opportunities.Finally, some highlights on the related key techniques and common issues in random access for massive IoT were concluded.